Effect of angular misalignment on the dynamic characteristics of externally pressurized air journal bearing. (February 2020) - Shi, Jianghai; Cao, Hongrui; Chen, Xuefeng
This paper studies the effect of angular misalignment on the dynamic characteristics of externally pressurized air journal bearing with four degrees of freedom. The linear perturbation method is applied to the Reynolds equation to obtain the steady-state equation and perturbation equations, and then the finite difference method and an iterative method are used to solve the Reynolds equation. Various eccentricity ratios and rotating speeds are taken into considerations for the comparisons of dynamic stiffness coefficients and damping coefficients of the air journal bearing under different tilt angles. In addition, the influences of perturbation frequency ratio on the dynamic performances of the air journal bearing are also estimated.